Influência das adições de Y e Ti sobre a microestrutura, comportamento mecânico e resistência à corrosão da liga Fe-25cr - Jesus, Thácylla Jamille Mecenas de (2020)
Due to their technical characteristics and low cost, ferritic stainless steels have been progressively standing out in recent years, especially when compared to austenitic stainless steels. However, despite their high resistance to corrosion, these materials are still susceptible to localized corrosion such as pitting and intergranular corrosion. In addition, in stainless steels with chromium content above 20%, the precipitation of intermetallic compounds can impair both corrosion resistance and mechanical properties. Thus, the addition of alloy elements should be investigated in order to verify the potential for resistance to localized corrosion and to evaluate its effect in relation to the intermetallic phases. Based on this understanding, this study aimed to characterize Fe-25Cr, Fe-25Cr-0.2Y and Fe-25Cr-0.2Ti alloys in order to evaluate the influence of Y and Ti elements on the microstructure, mechanical behavior and resistance corrosion, in addition to comparing them with stainless steels 430 and 304. The results show that the low concentrations of Y and Ti were not effective to refine Fe-α grains. The Fe-25Cr and Fe25Cr-0.2Y alloys were susceptible to the formation of intermetallic phases. However, the alloy with the addition of titanium promoted only the formation of nitrides and titanium carbides (TiN and TiC). Finally, the Fe-25Cr alloy reached the highest hardness value and the Fe-25Cr-0.2Ti alloy obtained the best corrosion resistance.